Emerging and other communicable diseases : (Institute of Water and Sanitation Development, 1996)
This manual is intended to help health professionals and public health coordinators working in emergency situations prevent, detect and control the major communicable diseases encountered by affected populations. Emergencies include complex emergencies and natural disasters (e.g. floods and earthquakes).